The Effect of The Use Of Information Technology and Implementation of Internal Controls on The Quality of Accounting Information - Fitria Handayani; Nur Zeina Maya Sari; Indri Utami (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2022)
The development of information technology has brought fundamental changes in business processes, from manual data processing to computerization. Good cooperation is needed to achieve quality internal control. Accounting information produced at this time must support increased productivity, efficiency and control which are important in facing competition. The purpose of this study was to find out how the influence of the Use of Information Technology and the Implementation of Internal Control on the Quality of Accounting Information at PT Gramedia Asri Media in Bandung City. The method used is a verification descriptive approach method. the population in this study were employees of PT Gramedia Asri Media as many as 56 people where the sampling method used was Simple Random Sampling probability sampling (determination by a random system). The results of the study show that the use of information technology has a significant effect on the quality of accounting information, so the statistical conclusion is that the application of internal control has a significant effect on the quality of accounting information